Presence System Using QR Code at MAN 02 Kepahiang Web Based - Harry Witriyono; Yuza Reswan; Giova Giova; Khairullah Khairullah (Penerbit Jurnal Indonesia, 2023)
MAN 02 Kepahiang is one of the schools in Kepahiang Regency which still uses a manual attendance process. In the process of teaching and learning activities students need a daily attendance process to process student attendance data which will be made as an attendance report which is one component of the assessment of the teaching and learning process. In implementing the manual attendance system carried out by students there are still deficiencies in terms of time efficiency in the process of recording attendance and preparing attendance reports for each class. In designing an attendance system using a QR Code in the form of a web base and using the PHP programming language with MySQL database processing also using the Waterfall method. This study aims to build an attendance system using the QR Code as a media for inputting student absentee data and in preparing student daily attendance reports it is made easier by having an attendance system built.